(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
A study of 36 athletes of ski cyclic types with high sports categories was carried out. Age was 18.6±0.5 years; weight 70±1.2 kg; BMI 22.4±0.7 units. Under the conditions of the plain, on the basis of a rerespiration test, groups with high and low resistance to hypoxia were identified. In the typified groups during the rest and bicycle ergometric load of submaximal power, indicators of respiratory metabolism were studied on the plain and in the middle-altitude region. It has been established that even among highly trained athletes with a large amount of stamina there are individuals with low hypoxic resistance, which has an influence on their ability to perform physical activity in the first days after the arrival at the mountains. At the same time, the indicators of pulse rate, minute volume of respiration, oxygen consumption, oxygen pulse and blood oxygenation have the greatest information content for assessing the functional backup of the body. Based on the correlations of these indicators, it is possible to assess the effectiveness of the adaptation process of athletes in the mountains and their readiness for competitive loads.